Advancements in lipid production research using the koji-mold Aspergillus oryzae and future outlook - Tamano, Koichi (Frontiers in Fungal Biology, 2024)
Research on enhancing the production of lipids, particularly polyunsaturated fatty acids that are considered important for health, has focused on improvement of metabolism as well as heterologous expression of biosynthetic genes in the oleaginous fungus Aspergillus oryzae. To date, the productivity and production yield of free fatty acids have been enhanced by 10-fold to 90-fold via improvements in metabolism and optimization of culture conditions. Moreover, the productivity of ester-type fatty acids present in triacylglycerols could be enhanced via metabolic improvement. Culturing A. oryzae in a liquid medium supplemented with non-ionic surfactants could also lead to the effective release of free fatty acids from the cells. The current review highlights the advancements made in this field so far and discusses the future outlook for research on lipid production using A. oryzae. I hope the contents are useful for researchers in this field to consider the strategy of increasing production of various valuable metabolites as well as lipids in A. oryzae.